Pengaruh Profitabilitas, Keputusan Investasi dan Keputusan Pendanaan terhadap Nilai Perusahaan - Anggreni, Ni Made Lisa; Wijaya, Putu Yudy; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Company Value reflects the assets owned by the company. The value of the company can be judged by its stable share price and increases in the long term. High stock prices make the company value also high. The higher the company value indicates the prosperity of the shareholders. This study aims to re-examine the effect of the variable profitability (ROE), investment decisions (PER) and funding decisions (DER) on firm value (PBV). This research was conducted at companies registered on the Liquid 45 index (LQ-45) on the Indonesia Stock Exchange in 2017-2019. The number of samples taken was 35 companies per year and 105 companies during the 2017-2019 period, using the purposive sampling research method. Data collection is carried out by accessing the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The analysis technique used is multiple linear regression analysis. The results of the study show that Profitability has a significant positive effect on firm value, Investment Decisions do not have a significant effect on Firm Value, Funding Decisions have a significant positive effect on Firm Value. The results of this study can be used as an alternative teaching resource to add material related to related courses, for information materials and input to management in order to improve company performance so that it is better in the future. This can be done by increasing Profitability (ROE), Investment Decision (PER), Funding Decision (DER). Thus the Company's Value (PBV) to the Company (LQ-45 Index) can be optimized and used as a recommendation for teaching resources or material for discussion in related subjects in lecture activities.